Telegram-Based Earthquake Early Warning - Arfanda Anugrah Siregar; Erwinsyah Simanungkalit; Nasrudin (Postgraduate, University of Mataram, 2025)
Earthquakes are one of the natural disasters whose arrival cannot be ascertained and have a very detrimental impact, both in terms of property losses and lives. Indonesia, with its very active tectonic plate conditions, often experiences earthquakes, so it needs an effective early warning system. BMKG has developed an early warning system that informs of earthquake events through various media. However, this system still has weaknesses in the speed of delivering information to the public. This research aims to design and make a prototype of an earthquake early warning tool that can send information in the form of notifications and warning alarms using the Telegram application. The use of Telegram as a medium for conveying information was chosen because of its high-speed, security, and accessibility. This research was carried out at the Telecommunications Laboratory, Politeknik Negeri Medan starting from the system design process, system implementation, MPU6050 sensor testing, LoRa SX1278 testing, microcontroller ESP32 testing, and Telegram BOT testing to detect earthquake vibrations and send earthquake scale notifications via the Telegram. It produced a prototype of an earthquake early warning tool that uses Telegram for the dissemination of warning information in real-time, so that people can more quickly take self-rescue actions.